Emergence of FinTech Ecosystem: A Case Study of ’bKash’ in Bangladesh - Hosen, Md Saikat; Rahman, Md. Habibur (Asian Business Review, 2023)
The cutting-edge economy has a lot of new wheels that turn the fortune of contemporary times. Monetary innovation is no question one of those. The new credit-only economy depends on these computerized monetary administrations. As of late, financial organizations, particularly banks, have become more subject to these howdy tech administrations. For the review, the information has been gathered by poll overview utilizing the positioned technique for examination utilizing SPSS, in which IT-related individuals have been studied. The study explains the characteristics and features of FinTech ecosystems emerging in Bangladesh. The "bKash" in Bangladesh is particularly appropriate for our research as it seeks to become a world-class Fintech hub for innovation by capitalizing on the opportunities brought by global technological trends. The study uses the CAS process model for analyzing biological systems, difficulties, and possibilities of fintech, especially bKash in Bangladesh. The results show that bKash has a promising future can significantly uplift Bangladesh’s economy.